As "mulheres malditas": crenças e práticas de feitiçaria no nordeste da América Portuguesa. - Silva, Nereida Soares Martins da (2012)
This work is devoted to the study of cases of witchcraft in the context of northeastern Portuguese America, it has as main sources, inquisitorial documentation for the period. In this work, we shall dwell on the analysis of cases of witchcraft perpetrated by women and our thematic approach focuses on magical beliefs and practices specifically European having as theoretical support history of mentalities. Throughout our research we have seen the convergence of an ancient stereotype Witch specimen whose model, expressed in literary records and iconography, has been made since ancient times and can also be seen in elements of popular religious culture developed of Portuguese America, and as among representatives of the dominant religion that worked here in defense of the faith. Therefore, this work is relevant historiographical field devoted to the subject in that the perspective from which it developed, introduces new elements to the analysis of a Historical Culture of witchcraft, in default of stringent temporal divisions heeded by historians, if consrói from permanence and change, a process where the elements that make up the image of the witch change, losing and acquiring meanings, under the auspices of religious hybridity from the ethnic touch so characteristic of our training.